Optimization of Human Capital in Improving Competitive Advantage of Higher Education through Institution’s Performance: A Case Study of Widyatama University - Sutisna, Deden; Wiludjeng SP, Sri; Riantani, Suskim; Eka Sumadhinata, Yelli (International Journal of Psychosocial Rehabilitation, 2020)
Human resources are a major factor in organizations or institutions, both profit-oriented and nonprofit. One organization that is not profit-oriented is higher education. To become a university that is able to compete with other universities, the organization must pay attention to the human capital (HC) owned by the higher education. Regarding the importance of human capital, which is part of intellectual capital (IC), it is necessary to conduct research that aims to find out how the conditions of human capital factors at Widyatama University are based on the criteria of BAN-PT. The research methods used are descriptive and comparative. The data used are secondary data because this research is only limited to qualitative analysis. The human capital dimension measured is the number of full-time professors, number and type of training, number of permanent lecturers, number of non-permanent lecturers (guest lecturers, extraordinary lecturers, expert lecturers), lecturer achievements (awards, grants, program funding), qualifications (total position) academic lecturer, academic lecturer competency (number of lecturers, S1, S2, S3) educations, and number of non-academic staff (librarians, laboratory staff, technicians, etc.). The results of the analysis of the data obtained indicate that the overall condition of Human Capital owned by Widyatama University is good because it is in accordance with the standards of BanPT